A good appearance spray-free ABS composite material and a preparation method thereof

CN123004075APending Publication Date: 2026-10-30CHONGQING ORINKO TECH CO LTD CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611083164.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有公开的免喷涂ABS技术(如CN105038095B、CN118638382A等)多采用ABS/PMMA简单复配基体,搭配单一偶联剂浸泡改性效果颜料,辅以常规润滑剂制备材料,一定程度上改善了制品外观效果,但在实际量产应用中仍存在诸多难以解决的技术缺陷

Benefits of technology

1、本发明采用超高分子有机硅、丙烯酸树脂双层包覆颜料,形成静电与位阻双重稳定结构,显著改善颜料团聚、掉粉、发白问题,制品外观光泽度与均匀性大幅提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of high polymer modified material, and particularly discloses a good-look spray-free ABS composite material and a preparation method thereof.The present application adopts an ABS / SAN / PMMA multi-element alloy base compounding system, is matched with organic silicon and acrylate resin double-layer coating modified effect pigment, is combined with nano-silicon dioxide, solid glass microbead and high polymer organic silicon ternary composite scratch-resistant additive, is matched with rheological modifier and halogen-free composite weather-resistant stabilizer, and a formula system with synergistically optimized performance and appearance is constructed; meanwhile, a low-temperature low-shear step extrusion process with main material main feeding and modified pigment middle-stage side feeding is adopted, so that the problem of high-temperature high-shear crushing of flaky pigment is effectively avoided.The present application significantly improves the flow mark, weld mark, agglomeration and ash defect of the spray-free ABS material, greatly improves the product surface gloss, scratch resistance and weather resistance, and has stable material mechanical properties, low VOC content, environmental protection compliance, can be one-time injection molding to replace the traditional spraying process, and is cost-effective and green and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer modified materials technology, and in particular to a good-looking, paint-free ABS composite material and its preparation method. Background Technology

[0002] ABS resin, as a general-purpose engineering plastic with excellent comprehensive performance, possesses advantages such as high impact strength, good dimensional stability, easy processing and molding, and outstanding cost performance. It is widely used in automotive interior and exterior parts, household appliance housings, and smart terminal exterior parts. To meet the decorative requirements of products, traditional ABS plastic parts generally adopt secondary decoration processes such as surface spraying and electroplating after injection molding. Although this can achieve aesthetic effects such as metallic luster and pearlescent texture, it suffers from problems such as cumbersome processes, long production cycles, and high processing costs. At the same time, the spraying process generates a large amount of VOC waste gas and waste paint residue, which does not meet the industry development requirements of green production and low-carbon environmental protection. Furthermore, the sprayed coating is prone to defects such as peeling, scratches, and loss of gloss, resulting in a high rework rate for plastic parts.

[0003] Paint-free ABS materials achieve decorative appearances through a single injection molding process by directly adding effect pigments such as metallic powder and pearlescent powder to the resin system. This eliminates the need for secondary spraying and represents a mainstream green technology to replace traditional spraying processes. It is gradually becoming more widespread in the home appliance and automotive industries. Existing publicly available paint-free ABS technologies (such as CN105038095B and CN118638382A) mostly use a simple ABS / PMMA composite matrix, combined with a single coupling agent to impregnate modified effect pigments, and supplemented with conventional lubricants to prepare the materials. While this improves the appearance of the products to some extent, many unresolved technical defects still exist in actual mass production applications.

[0004] The core shortcomings of existing technologies are concentrated in the following points: First, effect pigments only use single-layer surface treatment, resulting in poor compatibility between pigments and resin matrices. They are prone to agglomeration and clumping during processing and storage, leading to problems such as graying, color difference, powdering, and whitening in injection-molded products, resulting in poor appearance consistency. Second, conventional paint-free materials have weak scratch and wear resistance, with surface pencil hardness generally lower than HB, making them prone to scratches during daily use and unable to meet the wear resistance requirements of high-end home appliances and automotive interiors. Third, the melt rheological properties are not well controlled, easily producing obvious appearance defects such as tiger stripes, water ripples, and weld lines during the injection molding of large, thin-walled, and complex plastic parts, resulting in a low yield rate. Fourth, effect pigments are often extruded together with all materials at high temperature and high shear, making the sheet-like pigment structure easily sheared and broken, significantly weakening the metallic pearlescent texture. Fifth, existing technologies are mostly based on pure virgin material formulations, which cannot be adapted to the resource utilization of recycled ABS, and the weather resistance system is singular. Long-term outdoor use can easily lead to loss of gloss, fading, and cracking, limiting application scenarios.

[0005] To address the industry pain points of existing paint-free ABS materials, such as poor pigment stability, numerous appearance defects, insufficient scratch resistance, weak weather resistance, and inability to be adapted to mass production of recycled materials, this invention develops a paint-free ABS composite material with low flow marks, high scratch resistance, and high appearance consistency, as well as its preparation method. Through synergistic innovation of the formulation system and preparation process, the defects of existing technologies are completely solved, taking into account appearance, performance, environmental protection, and mass production adaptability. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the existing technology and to propose a good-looking, paint-free ABS composite material and its preparation method.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A good-looking, paint-free ABS composite material and its preparation method are disclosed, comprising the following raw materials in parts by weight: 40-70 parts of high-flow ABS resin, 10-20 parts of SAN resin, 5-15 parts of PMMA resin, 3-8 parts of high-adhesion ABS powder, 1-5 parts of double-layer coated modified effect pigment, 1.5-4 parts of composite scratch-resistant additive, 0.5-2 parts of composite weather-resistant stabilizer, 0.2-1 parts of rheology modifier, and 0.3-1 parts of processing lubricant; wherein the double-layer coated modified effect pigment is coated with a coupling agent layer and a thermoplastic resin layer from the inside out; the composite scratch-resistant additive is a composite system of nano-silica, ultrafine solid glass microspheres, and ultra-high molecular weight organosilicon.

[0008] Preferably, the particle size D50 of the double-layer coated modified effect pigment is 9–23 μm.

[0009] Preferably, the coupling agent layer is a silane coupling agent or a titanate coupling agent, and the thermoplastic resin layer is an acrylate resin.

[0010] Preferably, in the composite scratch-resistant additive, the nano-silica particles have a diameter of 20-50 nm, the ultrafine solid glass microspheres have a diameter of 5-10 μm, and the mass ratio of ultra-high molecular weight organosilicon, nano-silica, and glass microspheres is 2:1:1.5.

[0011] Preferably, the high-flow ABS resin has a melt index ≥30g / 10min at 220℃ / 10kg.

[0012] Preferably, the composite weather stabilizer is a halogen-free system, which is composed of hindered amine light stabilizers, benzotriazole UV absorbers and main and auxiliary composite antioxidants.

[0013] Preferably, the rheology modifier is an acrylate rheology modifier.

[0014] Preferably, the high-flow ABS resin further comprises 30% to 50% recycled ABS resin by weight of the total ABS resin, and 0.5 to 1.5 parts by weight of chain extender compatibilizer.

[0015] A method for preparing ABS paint-free composite material, used to prepare the above-mentioned ABS paint-free composite material, includes the following steps: (1) Premixing the main material: according to the ratio, high-flow ABS resin, SAN resin, PMMA resin, ABS high-rubber powder, composite weather-resistant stabilizer, rheology modifier and processing lubricant are put into a high-speed mixer and stirred at room temperature for 5-10 minutes to obtain a mixture of main materials; (2) Melting and plasticizing: the mixture of main materials is fed into the main feed port of a twin-screw extruder and melted and plasticized using a stepped temperature control of 180-225℃ and a twin-screw extruder; (3) Precise side feeding: double-layer coated modified pigments are quantitatively fed into the middle section side feed port of the twin-screw extruder; (4) Molding and granulation: the melt-blended material is extruded through a die head, water-cooled traction, air-dried and granulated, and screened to remove powder, finally obtaining the finished ABS paint-free composite material.

[0016] Preferably, the process parameters for the twin-screw extruder are set as follows: screw speed 300-450 r / min.

[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses ultra-high molecular weight organosilicon and acrylic resin to double-coat pigments, forming a dual-stabilized structure of electrostatics and steric hindrance, which significantly improves the problems of pigment agglomeration, powdering, and whitening, and greatly enhances the gloss and uniformity of the product appearance.

[0018] 2. The ternary composite scratch-resistant additive system synergistically enhances the surface pencil hardness of the material to H~2H, and improves the wear resistance by more than 40% compared with the traditional formula, effectively improving the shortcoming of poor scratch resistance of traditional paint-free materials.

[0019] 3. ABS / SAN / PMMA multi-resin alloy combined with acrylate rheology modifiers precisely controls the melt rheological properties, completely eliminating appearance defects such as tiger stripe patterns, water ripples, and weld lines caused by injection molding of large and thin-walled plastic parts.

[0020] 4. The pigment is fed from the middle section and extruded at low temperature and low shear to preserve the complete flake structure of the pigment to the greatest extent, avoid shearing and breakage and graying, and ensure excellent batch appearance consistency.

[0021] 5. The halogen-free composite weather-resistant system is suitable for long-term outdoor use, and is also compatible with 30% to 50% recycled ABS modification. It realizes the resource utilization of solid waste while ensuring performance, making it green, environmentally friendly, cost-reducing and efficiency-enhancing.

[0022] 6. One-time injection molding eliminates the need for painting, simplifying production processes, reducing VOC emissions, and making it suitable for mass production of automotive interior and exterior trims and high-end home appliances. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0024] Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0025] All raw materials used in the embodiments and comparative examples of this patent are mainstream commercial industrial brands. Their performance parameters match the formulation design requirements of this invention. They are stable in origin, mass-producible, and traceable. The specific raw material specifications, brands, and manufacturers are as follows: 1. High-flow ABS resin: Grade 750A, Chi Mei Industrial Co., Ltd., Taiwan, China; melt index 32g / 10min (220℃ / 10kg), high flow, low odor, high gloss, suitable for thin-walled large parts injection molding without spraying, is the special matrix resin of this invention.

[0026] 2. SAN (AS) resin: grade PN-118, Chi Mei Industrial Co., Ltd., Taiwan, China; high transparency, high rigidity, excellent chemical resistance, improves melt uniformity and product surface smoothness, and improves alloy compatibility and stability.

[0027] 3. PMMA resin: Grade CM-205, Chi Mei Industrial Co., Ltd., Taiwan, China; High light transmittance, ultra-high gloss, excellent weather resistance, effectively improves the surface density and mirror texture of paint-free products, and suppresses fogging defects in spraying.

[0028] 4. ABS high-adhesion powder: Grade HR-181, Shandong Qifeng New Materials; Butadiene content 65%, high toughness, high grafting rate, improves the material's impact resistance, and improves the compatibility between pigments and matrix.

[0029] 5. Recycled ABS resin: Grade I recycled ABS from household appliance crushing, Guangdong Xinyuan Plastics; after sorting, impurity removal, filtration and VOC removal treatment, the purity is ≥98%, which is suitable for the 30% to 50% replacement ratio of this invention.

[0030] 6. Double-layer coated modified effect pigments (1) Flake aluminum powder: grade ZF-201, Changzhou Zhongfu New Materials; virgin flake floating aluminum powder, D50=16μm, particle size range 9~23μm; inner layer coated with silane coupling agent KH-550 (Nanjing Chuangshi Chemical), outer layer coated with acrylate copolymer resin (BASF Joncryl-611), which is a double-layer coating structure customized for this invention.

[0031] (2) Pearl powder: Grade S-215, Zhejiang Ruier New Materials; mica-based pearl powder, with high whiteness and strong transparency, suitable for the high-gloss, paint-free appearance of home appliances.

[0032] 7. Ternary composite scratch-resistant additive components (1) Ultra-high molecular weight organosilicon: grade PPA-788, Dow Corning, USA; ultra-high molecular weight silicone powder, low precipitation and migration resistance; (2) Nano silica: Grade VK-SP30, Xuancheng Jingrui New Materials; Particle size 20-50nm, hydrophobic; (3) Ultrafine solid glass microspheres: grade H-10, Shanxi Hainuo Technology; particle size 5~10μm, high hardness, low oil absorption; the three are strictly compounded according to the mass ratio of 2:1:1.5.

[0033] 8. Composite weather stabilizer (halogen-free system) (1) Hindered amine light stabilizer: UV-944, BASF; (2) Benzotriazole UV absorber: UV-327, BASF; (3) Main and auxiliary compound antioxidants: main antioxidant 1010, auxiliary antioxidant 168 (BASF compound system), halogen-free, low VOC, and compatible with automotive interior ELV standards.

[0034] 9. Acrylic rheology modifier: KM-355, Kaneka Chemicals, Japan; a high-efficiency melt rheology modifier that balances shear viscosity and eliminates flow marks and weld lines.

[0035] 10. Processing lubricant: EVA wax LW-101, Shandong Luyan Chemical; mainly internal lubrication, low precipitation, does not affect coating adhesion and surface gloss.

[0036] 11. Chain extender compatibilizer: Epoxy functionalized chain extender (ADR-4370), BASF, Germany; a polymer chain extender specifically designed to repair broken molecular chains in recycled ABS and improve the compatibility and mechanical stability of the recycled material system.

[0037] 12. The single-layer coated aluminum powder used in the comparative example: conventional KH-550 single-layer coupling agent modified aluminum powder, grade ZF-201S, Changzhou Zhongfu New Materials (common standard product on the market, without acrylic outer layer sealing).

[0038] 13. The single silicone lubricant used in the comparative example: ordinary silicone powder 601, Dow Corning general grade (non-ultra-high molecular weight, no nano-powder compound).

[0039] To better illustrate the technical solution and beneficial effects of the present invention, three sets of examples and two sets of comparative examples are set up. Each raw material is prepared in strict accordance with the weight ratio and a unified preparation process and industry-standard testing are adopted.

[0040] Unified preparation process: The main material is mixed at high speed for 5-10 minutes. The temperatures of the first to tenth zones of the twin-screw extruder are 170℃, 180℃, 190℃, 200℃, 205℃, 205℃, 200℃, 210℃, 215℃, and 215℃, respectively. The die head temperature is 220℃, the screw speed is 350 r / min, the main feed frequency is 20 Hz, the pigment middle section side feed frequency is 5 Hz, and the process is water-cooled, air-dried, pelletized, and screened to remove powder.

[0041] Example 1 Optimal ratio: 55 parts high-flow ABS resin, 15 parts SAN resin, 10 parts PMMA resin, 5 parts high-adhesion ABS powder, 3 parts double-coated aluminum powder, 2.5 parts composite scratch-resistant additive, 1 part composite weather-resistant stabilizer, 0.5 parts acrylate rheology modifier, and 0.6 parts processing lubricant.

[0042] Example 2 High gloss, appliance-specific system: 50 parts high-flow ABS resin, 18 parts SAN resin, 12 parts PMMA resin, 6 parts high-adhesion ABS powder, 2.5 parts double-coated pearlescent powder, 3 parts composite scratch-resistant additive, 1.2 parts composite weather-resistant stabilizer, 0.6 parts rheology modifier, and 0.7 parts processing lubricant.

[0043] Example 3 Environmentally friendly recycled materials and green mass production system: 30 parts of new ABS resin, 25 parts of recycled ABS resin, 15 parts of SAN resin, 8 parts of PMMA resin, 5 parts of high-adhesion ABS powder, 3 parts of double-coated aluminum powder, 2.5 parts of composite scratch-resistant additive, 1 part of composite weather-resistant stabilizer, 0.5 parts of rheology modifier, 0.6 parts of processing lubricant, and 1 part of chain extender compatibilizer.

[0044] Comparative Example 1 Traditional single-layer pigment coating, conventional solutions on the market: The formula is the same as in Example 1, except that the double-layer coated aluminum powder is replaced with ordinary organosilicon single-layer coated aluminum powder, and the other raw materials and processes are exactly the same.

[0045] Comparative Example 2 Single scratch-resistant additive - traditional formulation: The formula is the same as in Example 1, except that the ternary composite scratch-resistant additive is replaced with an equal amount of single organosilicon lubricant, and the other raw materials and processes are exactly the same.

[0046] Unified testing standards: gloss (60° angle), pencil hardness, appearance flow mark grade, 500h UV weathering test, and appearance consistency evaluation.

[0047] The composite materials of Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, and the results are shown in Table 1: Table 1 As can be seen from the data in Table 1 above, the paint-free ABS composite material prepared by this invention has excellent appearance and weather resistance. This invention addresses the common technical bottlenecks in existing paint-free ABS materials, such as easy agglomeration of effect pigments, obvious injection molding flow marks and weld lines, insufficient scratch and abrasion resistance, poor weather resistance, weak appearance consistency, and inability to adapt to large-scale applications of recycled materials. It innovatively develops a low-flow-mark, high-scratch-resistant paint-free ABS composite material based on double-layer coated effect pigments, a ternary composite scratch-resistant system, and a multi-component resin alloy, along with its segmented side-feeding low-temperature preparation process. This invention systematically solves many inherent defects of traditional paint-free materials from four dimensions: pigment interface modification, matrix rheology control, surface property enhancement, and molding process optimization, through deep synergistic optimization of the formulation system and processing technology.

[0048] Through multiple sets of examples and comparative experiments, it has been verified that the material of this invention significantly improves the surface gloss, appearance uniformity, scratch resistance, hardness, and aging resistance of the products compared to traditional formulations. It can reliably eliminate appearance problems such as tiger-skin patterns, water ripples, and color differences in weld lines that occur during the injection molding of large, thin-walled, and complex plastic parts. The products exhibit good batch consistency and a high yield rate. Furthermore, the formulation system of this invention is compatible with 30%–50% modified recycled ABS resin, achieving the resource-based reuse of plastic solid waste while ensuring that the material's appearance quality and performance are not diminished. This aligns with national green manufacturing, low-carbon environmental protection, and circular economy industrial policies. Moreover, the overall formulation is halogen-free and low in VOCs, meeting RoHS, ELV, and other environmental access standards for the automotive and home appliance industries.

[0049] Furthermore, this invention employs a differentiated low-shear extrusion process with main material feeding and pigment side feeding in the middle section, effectively protecting the intact microstructure of the flake pigment and completely solving the problems of pigment breakage, graying, and reduced texture in traditional blending processes. The process is simple, highly controllable, and suitable for large-scale industrial production. In summary, this invention's technical solution is highly innovative, significantly improves performance, is highly feasible for mass production, and has a wide range of applications. It effectively overcomes the technical shortcomings of existing similar products and possesses extremely high market application value, economic benefits, and social and environmental value.

[0050] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0051] The foregoing has shown and described the basic principles, main features, and advantages of this application. Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made to this application without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of the claims of this application.

Claims

1. An ABS paint-free composite material, characterized in that, It is composed of the following raw materials in parts by weight: 40-70 parts of high-flow ABS resin, 10-20 parts of SAN resin, 5-15 parts of PMMA resin, 3-8 parts of ABS high-adhesion powder, 1-5 parts of double-layer coated modified effect pigment, 1.5-4 parts of composite scratch-resistant additive, 0.5-2 parts of composite weather-resistant stabilizer, 0.2-1 parts of rheology modifier, and 0.3-1 parts of processing lubricant; the double-layer coated modified effect pigment is coated with a coupling agent layer and a thermoplastic resin layer from the inside to the outside; the composite scratch-resistant additive is a compound system of nano-silica, ultrafine solid glass microspheres and ultra-high molecular weight organosilicon.

2. The ABS paint-free composite material according to claim 1, characterized in that, The particle size D50 of the double-layer coated modified effect pigment is 9-23 μm.

3. The ABS paint-free composite material according to claim 1, characterized in that, The coupling agent layer is a silane coupling agent or a titanate coupling agent, and the thermoplastic resin layer is an acrylate resin.

4. The ABS paint-free composite material according to claim 1, characterized in that, In the composite scratch-resistant additive, the nano-silica particles have a diameter of 20-50 nm, the ultrafine solid glass microspheres have a diameter of 5-10 μm, and the mass ratio of ultra-high molecular weight organosilicon, nano-silica, and glass microspheres is 2:1:1.

5.

5. The ABS paint-free composite material according to claim 1, characterized in that, The high-flow ABS resin has a melt index ≥30g / 10min at 220℃ / 10kg.

6. The ABS paint-free composite material according to claim 1, characterized in that, The composite weather stabilizer is a halogen-free system, composed of hindered amine light stabilizers, benzotriazole UV absorbers, and main and auxiliary composite antioxidants.

7. The ABS paint-free composite material according to claim 1, characterized in that, The rheology modifier is an acrylate rheology modifier.

8. The ABS paint-free composite material according to claim 1, characterized in that, The high-flow ABS resin also contains 30% to 50% recycled ABS resin by weight of the total ABS resin, and 0.5 to 1.5 parts by weight of chain extender compatibilizer.

9. A method for preparing an ABS paint-free composite material, characterized in that, The preparation of the ABS paint-free composite material according to any one of claims 1-8 includes the following steps: (1) Premixing of main materials: according to the formula, high-flow ABS resin, SAN resin, PMMA resin, ABS high-rubber powder, composite weather-resistant stabilizer, rheology modifier and processing lubricant are put into a high-speed mixer and stirred at room temperature for 5-10 minutes to obtain a mixture of main materials; (2) Melting and plasticizing: the mixture of main materials is fed into the main feed port of a twin-screw extruder and melted and plasticized using a twin-screw extruder with stepped temperature control of 180-225℃; (3) Precise side feeding: double-layer coated modified pigments are quantitatively fed into the side feed port of the middle section of the twin-screw extruder; (4) Molding and granulation: the melt-blended material is extruded through a die head, water-cooled traction, air-dried and granulated, and screened to remove powder, finally obtaining the finished ABS paint-free composite material.

10. The method for preparing an ABS paint-free composite material according to claim 9, characterized in that, The process parameters for the twin-screw extruder are set as follows: screw speed 300-450 r / min.

Citation Information

Patent Citations

  • A spray-free and flow-line-free ABS composite material and its preparation method

    CN105038095B

  • Spraying-free material, preparation method thereof and spraying-free workpiece

    CN118638382A